2019
DOI: 10.1101/529016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanically activated Piezo channels control outflow tract valve development through Yap1 and Klf2-Notch signaling axis

Abstract: Mechanical forces are well known for modulating heart valve developmental programs. Yet, it is still unclear how genetic programs and mechanosensation interact during heart valve development. Here, we assessed the mechanosensitive pathways involved during zebrafish outflow tract (OFT) valve development in vivo. Our results show that the hippo effector Yap1, Klf2, and the Notch signaling pathway are all essential for OFT valve morphogenesis in response to mechanical forces, albeit active in different cell layer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…This is yet another example for the complexity of Hippo pathway activity within the multi-tissue comprising heart. These findings add Piezo1 to the repertoire of mechanosensitive modulators of Hippo signaling during cardiac valve formation in zebrafish (Duchemin et al, 2019a). However, the precise molecular mechanisms of that crosstalk are currently unknown and remain an exciting topic for future investigations.…”
Section: The Mechanosensitive Piezo1 Channel and Yap1 Signaling Modulate Outflow Tract Valvulogenesismentioning
confidence: 76%
See 2 more Smart Citations
“…This is yet another example for the complexity of Hippo pathway activity within the multi-tissue comprising heart. These findings add Piezo1 to the repertoire of mechanosensitive modulators of Hippo signaling during cardiac valve formation in zebrafish (Duchemin et al, 2019a). However, the precise molecular mechanisms of that crosstalk are currently unknown and remain an exciting topic for future investigations.…”
Section: The Mechanosensitive Piezo1 Channel and Yap1 Signaling Modulate Outflow Tract Valvulogenesismentioning
confidence: 76%
“…Biomechanical forces that can impact Hippo signaling include hemodynamics, cell stretching, cellular crowding/tension, junctional forces, mechanical coupling, and actomyosin cytoskeletal rearrangements (Figure 3D). Upon mechanical stimulation, mechanosensation and force transmission toward Hippo signaling proteins involves the cell junctional protein Cadherin-5 (Bornhorst et al, 2019) and the cation ion channels Piezo1/2 (Duchemin et al, 2019a). This causes changes in gene expression profiles involving the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathways that play crucial role in atrioventricular development are emerging to be involved also in shaping the outflow tract. These include the Yap1 klf2a/Notch axis (Duchemin et al, 2019) as well as Tgfβ (Boezio et al, 2020). Based on that, it is not surprising that prkd2 mutants show defects both in the bulbus arteriosus (initially) and the atrioventricular valve.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies of small animal models provided evidence that congenital malformations can be elicited by alteration of the mechanical flow environment (Tobita and Keller 2000;Kowalski et al 2014;Tobita et al 2002), and identified mechanobiological mechanism for such malformations (Duchemin et al 2019;Groenendijk et al 2005). It is thus important to understand the biomechanical environment of the embryonic heart, and understand what patterns of blood flow and forces may lead to the malformations.…”
Section: Introductionmentioning
confidence: 99%